Experimental study on the drag characteristic and thermal performance of non-uniform fillings for wet cooling towers under crosswind conditions. (25th July 2018) - Zhou, Yang; Wang, Kun; Gao, Ming; Dang, Zhigang; He, Suoying; Sun, Fengzhong
Highlights: The performance of non-uniform fillings for wet cooling towers is studied in lab. Non-uniform fillings can alleviate adverse effect of crosswind on cooling towers. P4 is optimal non-uniform pattern if giving the priority to energy conservation. P3 is the optimal pattern if considering water-saving characteristic preferentially. Abstract: A thermal-state model experimental study was performed to investigate the drag characteristic and thermal performance of non-uniform fillings for wet cooling towers under crosswind conditions, several valuable performance parameters, including cooling efficiency, drag coefficient, ventilation rate, heat transfer coefficient and Merkel number, etc. were analyzed in this paper. Experimental researches proved that the non-uniform fillings are not sensitive to the crosswind, and can alleviate the adverse effect of crosswind on wet cooling towers. From the perspective of drag characteristic and thermal performance, the P4 pattern is the optimal non-uniform pattern under crosswind conditions, which has the higher ventilation rate, heat transfer coefficient, Merkel number and lower drag coefficient within the experimental crosswind velocity range. However, the P3 pattern has the lower evaporation loss and the outstanding relatively water-saving performance. Therefore, studies in this paper revealed that the optimal non-uniform pattern should be selected by terms of comprehensive consideration of energy conservation and water-saving. The P4 pattern is the optimal non-uniform pattern if giving the priority to energy conservation, and conversely, the P3 is the optimal pattern if considering water-saving characteristic preferentially.